Tributyltin: A Bottom–Up Regulator of the Crangon crangon Population? - Parmentier, Koen F. V.; Verhaegen, Yves; De Witte, Bavo P.; Hoffman, Stefan; Delbare, Daan H. R.; Roose, Patrick M.; Hylland, Ketil D. E.; Burgeot, Thierry; Smagghe, Guy J.; Cooreman, Kris (Frontiers in Marine Science, 2019)
The restrictions and the concerted action of the global ban on the use and presence of tributyltin (TBT) in marine applications to protect ecosystems in the marine environment in 2008 was mainly based on the economic impact on shellfish industries and the dramatic extinction of local mollusc populations in the past. In contrast to the vast datasets on effects on molluscs, the knowledge on impacts on species from other taxa remained in the uncertain until almost two decades ago. The assumption on a long-term TBT-mediated pernicious metabolic bottom-up regulation of the crustacean Crangon crangon population was provoked by the outcome of an EU-project ‘Sources, Consumer Exposure and Risks of Organotin Contamination in Seafood’. This study reported high TBT body burdens in C. crangon in 2003, at the start of the transition period to the global ban. Experimental research on the TBT impact in C. crangon focused on agonistic interference with natural ecdysteroid hormones at the metabolic pathways regulating growth and reproduction and the biogeochemical distribution of the chemical. In this paper, metabolic, topical and population-relevant biological endpoints in C. crangon and other crustaceans are evaluated in relation to the temporal and spatial trends on TBT’s occurrence and distribution in the field during and after the introduction of the tributyltin restrictions and endocrine-related incidents. Arguments are forwarded to relate the German Bight incident on growth and reproduction failure in the C. crangon population, despite the lack of direct evidence, to the pernicious impact of tributyltin in 1990/91 and previous years. The extreme occurrence of TBT in C. crangon from other parts of the southern North Sea and evidence on the high body burdens as dose metrics of exposure also feeds the suspicion on detrimental impacts in those areas. This paper further demonstrates the complexity of distinguishing and assessing the individual roles of unrelated stressors on a population in an integrated evaluation at the ecosystem level.